UJI KEPEKAAN ANTIBIOTIK GOLONGAN KUINOLON TERHADAP BAKTERI Pseudomonas aeruginosa PENGHASIL MBL (METALLO BETA LAKTAMASE) PADA ISOLAT KLINIS KOLEKSI LABORATORIUM MIKROBIOLOGI FAKULTAS KEDOKTERAN UNIVERSITAS GADJAH MADA PERIODE 2011 HINGGA 2013 - , FERRY AGUNG PRASETYO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Asia is now becoming the epicentrum of antibiotic resistance dissemination, which requires more attention from related parties. Ineffectiveness and inefficiency of medical interventions did not only influence patient morbidity and mortality rate, but influence the amount of price that patients need to expense for medical treatments. Metallo Beta Lactamase (MBL)-producing P. aeruginosa took part in nosocomial outbreaks happened in a number of health cares. So, surveillance of resistant bacteria dissemination and knowing the suitable choices of treatments are now being very necessary to be studied further. Objective: The objective of this study is to know the pattern of Quinolone class antibiotics sensitivity towards Metallo Beta Lactamase-producing Pseudomonas aeruginosa. Method: Subjects of this study were Quinolone class antibiotics and Metallo Beta Lactamase-producing P. aeruginosa. Experiment was done to 25 clinical isolates of P. aeruginosa from Department of Microbiology Faculy of Medicine Universitas Gadjah Mada period 2011 until 2013. Antibiotic sensitivity test towards bacteria was done by using Kirby-Bauer method, based on CLSI standard. Result: Proportion of MBL enzyme-producing P.aeruginosa in clinical isolates from Department of Microbiology Faculty of Medicine Universitas Gadjah Mada period 2011 until 2013 showed low percentage, which was only 12% from 25 tested clinical isolates. Four antibiotics from Quinolone class antibiotic have low sensitivity level towards MBL-producing P. aeruginosa, which are 33.3% in Ciprofloxacin, Levofloxacin, Norfloxacin, and Ofloxacin. Conclusion: Quinolone class antibiotics are not sensitive towards Metallo Beta Lactamase-producing P. aeruginosa.